The COVID-19 awareness and safety recommendations response (adherence) rate of people living in Addis Ababa, Ethiopia - Gebretsadik, Heron Gezahegn (Orapuh Journal, 2021)
Introduction Ethiopia reported its first case of COVID-19 at the beginning of March 2020. Although the extent of the outbreak in Africa has remained unpredictable, it can be said that some of its effects are already observable in the economy, politics, and society. Lack of disease awareness and widespread poverty in the continent of Africa is supposed to be challenging to contain the spread of the disease. Purpose The study aimed to assess the COVID-19 awareness and safety recommendations response (adherence) rate of people living in Addis Ababa, Ethiopia. Materials and Methods Descriptive epidemiology and ethnography designs were used to assess the COVID-19 awareness and safety recommendations response (adherence) rate of people living in Addis Ababa. In this study, a mixed-method approach, in which the quantitative and qualitative paradigms are used at different phases was adopted. The relevant data were collected using questionnaires. Results A total of 1118 respondents and three key informants (ethnographers) were involved in this study. A significant portion of the respondents was found to be well aware of COVID-19. Out of the 1118 respondents, 99.6% (n=1114) have reported at least a single symptom and mode of transmission of the disease. On contrary, a poor adherence rate was reported by the respondents and ethnographers. For example, only 25% (n=280) and 22.3% (249) of the total study participants abided by the stay-at-home and physical distancing recommendations, respectively. Furthermore, only 55% (n=589) of the respondents used to wash their hands correctly. Negligence was also reported among 70.1% (n=714) of the respondents. Conclusion Both the descriptive epidemiology and the ethnographic approaches have revealed that the COVID-19 safety recommendations adherence rate of residents in Addis Ababa was found to be insufficient. In contrast, the disease awareness was significantly high. Therefore, more public and media campaigns need to be initiated to improve people’s adherence to the COVID-19 preventive measures. Furthermore, accessibility to face masks, gloves, sanitary materials, and non-crowded public transport should be ascertained to contain the spread of the disease.